Chronic exposure to Tributyltin induces brain functional damage in juvenile common carp (Cyprinus carpio) - Li, Zhi-Hua; Li, Ping; Shi, Ze-Chao (PLoS One, 2015)
The aim of the present study was to investigate the effect of Tributyltin (TBT) on brain function and neurotoxicity of freshwater teleost. The effects of long-term exposure to TBT on antioxidant related indices (MDA, malondialdehyde; SOD, superoxide dismutase; CAT, catalase; GR, glutathione reductase; GPx, glutathione peroxidase), Na+-K+-ATPase and neurological parameters (AChE, acetylcholinesterase; MAO, monoamine oxidase; NO, nitric oxide) in the brain of common carp were evaluated. Fish were exposed to sublethal concentrations of TBT (75 ng/L, 0.75 μg/L and 7.5 μg/L) for 15, 30, and 60 days. Based on the results, a low level and short-term TBT-induced stress could not induce the notable responses of the fish brain, but long-term exposure (more than 15 days) to TBT could lead to obvious physiological-biochemical responses (based on the measured parameters). The results also strongly indicated that neurotoxicity of TBT to fish. Thus, the measured physiological responses in fish brain could provide useful information to better understand the mechanisms of TBT-induced bio-toxicity.
Keywords: Carps; kapři; Animals; Oxidative Stress; Antioxidants; zvířata; Trialkyltin Compounds; oxidační stres; chemické látky znečišťující vodu; Brain; trialkylcínové sloučeniny; Water Pollutants, Chemical; antioxidancia; mozek